Testimony [compact disc, unabridged] - Turow, Scott (Hachette Audio, 2017)
Assigned to investigate the unsolved disappearance of an entire Gypsy refugee camp during the Bosnian War, Bill ten Boom, a disillusioned American prosecutor, navigates a host of suspects while uncovering disturbing alliances and betrayals.